The evolution of warfare from conventional to a digital battlefield: an analysis of cyber technology and artificial intelligence in the Lebanese-Israel conflicts - Sereina Khalifeh (Defense and Security Studies)
This study will evaluate the transition from conventional combat methods to a technology-driven battlefield. In particular, the Lebanon-Israel conflict serves a crucial case study to analyze how digital tools and AI reshape battlefield strategies, operational efficiency, and psychological warfare, triggering a broader evolution in modern military doctrine. This study will tackle a longitudinal comparison of digital strategy evolution in a single dyadic conflict zone. It adds to fields of security studies, cyberwarfare strategy, and AI-driven conflict analysis by analyzing how asymmetric technological adoption constructs long-term power dynamics. Through a theoretical lens of realism and a complementary military geopolitical framework, this research will analyze the impact of cyber warfare, AI-driven decision-making, intelligence, and precision missile systems on military strategies, political decision-making, and regional security.